2009
DOI: 10.1508/cytologia.74.417
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Genotoxicity Studies of Cefotaxime

Abstract: Summary Cefotaxime is a semisynthetic broad-spectrum bactericidal antibiotic derived from cephalosporin C. The aim of this work is to evaluate the genotoxic effect induced by intraperitoneal (i.p.) administration of cefotaxime at different doses (260, 520 and 1040 mg/kg b.wt.). The induction of sister chromatid exchanges "SCE's" in mouse bone marrow cells, chromosomal aberrations in mouse primary spermatocytes after repeated treatment (4, 7 and 10 d), and morphological sperm abnormalities were determined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In previous studies, it has been reported that several antibiotics especially the cephalosporins like cefixime, cefaclor, cefadroxil, cefotaxime induce chromosomal aberrations. 8,9 However, there is paucity of reports regarding the genotoxic potential of ceftriaxone. Since ceftriaxone is commonly used drug, it is prudent to screen it for genotoxicity.…”
mentioning
confidence: 99%
“…In previous studies, it has been reported that several antibiotics especially the cephalosporins like cefixime, cefaclor, cefadroxil, cefotaxime induce chromosomal aberrations. 8,9 However, there is paucity of reports regarding the genotoxic potential of ceftriaxone. Since ceftriaxone is commonly used drug, it is prudent to screen it for genotoxicity.…”
mentioning
confidence: 99%